ChemInform Abstract: A New Recyclable 1, 4‐bis(3‐methylimidazolium‐1‐yl)butane Ditribromide [bMImB]·(Br3)2 Ionic Liquid Reagent for Selective Bromination of Anilines or Phenols and α‐Bromination of Alkanones under Mild Conditions. Issue 3 (January 2015) - Veisi, Hojat; Sedrpoushan, Alireza; Mohammadi, Pourya; Faraji, Ali Reza; Sajjadifar, Sami
Abstract A novel ditribromide ionic liquid reagent with high active bromine content, which acts as a good brominating agent is described.